Antimicrobial compounds from Calophyllum canum - Sheikh, Hasan I; Darnis, Deny Susanti; Bakhtiar, M. Taher; Ahmed, Hanad; Syed Osman Idid, Syed Zahir Idid (2010)
Calophyllum species have been used in traditional medicine for its therapeutic properties in many tropical climate counteries. Calopyllum canum locally known as bintagor merah has been isolated and tested for its antimcirobial activity. Stembarks of C. canum were extracted by soxhlet extraction with n-hexane, ethyl acetate and then methanol, successively. The antimictovial activity was carried out by disc difussion method and determination of MIC and MBC values. n-Hexane extracts was active against S.aureus and B.subtili, while methanol extract inhibited the growuth of S.aureus, B.subtilis and E.coli. Ethyl acetate extract was also active against S.aureus and B.subtilis. Both n-haxena and methanol extracts were furhter subjected to column chramotography by guiding of its antimicrobial actvity. Four compounds were sucesfully isolated.; two (D1 and D2) from n-hexane extract and two from methanol (CCM1 and CCM2). The compondsD1 and d2 were active against S.aureus and B. anthracis. While CCM1 and CCM2 were active against S.aureus. Furhter research need to be done to identify the structure of the active compounds and investigate their mood of action.